PENGEMBANGAN PERMAINAN ROBOT PINTAR UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KOMPUTASIONAL PADA PEMBELAJARAN KODING DAN KECERDASAN ARTIFISIAL - Popon Siti Fauziah; Ririn Widiyasari; Muhamad Sofian Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Computational thinking is an essential competency as it supports the development of problem-solving skills and fosters critical thinking required in the digital era. Furthermore, the government has integrated Coding and Artificial Intelligence learning into the educational curriculum, which includes learning outcomes related to computational thinking. However, the urgency of developing computational thinking is not aligned with students’ current abilities, which remain at a low level. This study aims to: (1) describe the product development process, (2) assess the feasibility of the product, and (3) examine the product’s effectiveness in improving computational thinking skills. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The analysis phase involved identifying needs, the design phase utilized Canva, the development phase included product creation and validation by material and media experts, the implementation phase conducted product trials, and the evaluation phase determined the feasibility of the Smart Robot game. The results indicated that the Smart Robot game is feasible (valid, practical, and effective) with a validity percentage of 83.61% (very valid), practicality of 86% (very practical), and an N-gain of 0.47 (medium category). The use of the Smart Robot in Coding and Artificial Intelligence learning effectively enhances students’ computational thinking skills.